MOLECULAR SPECTROSCOPIC ANALYSIS OF THE FUNCTIONAL COMPOSITION OF SILK FIBRON (European Journal of Emerging Technology and Discoveries, 2025)
X-ray diffraction analysis of the samples showed that in the range of diffraction angles considered, crystalline reflexes were observed at 2θ=13.09°, 18.63°, 21.21°, 25.33° and 30.39°, which are characteristic of fibroin.